Legal Protection Mechanism for Pension Fund Beneficiaries Against Maladministration of Pension Payments - Lihawa, Rahmad; Thalib, Mutia Cherawaty; Sarson, Moh. Taufiq Zulfikar (Estudiante Law Journal, 2025)
This research discusses the legal protection mechanisms available to pension beneficiaries against maladministration in pension fund payments by partner banks of PT Taspen (Persero), specifically Bank SulutGo in the Gorontalo region. The background of this study stems from the fact that pension funds are a constitutional right of citizens, as stated in Article 28H paragraph (3) of the 1945 Constitution of the Republic of Indonesia, and are also a form of social security guaranteed by Law No. 40 of 2004 concerning the National Social Security System. However, in practice, maladministration cases such as unilateral account blocking, transfer delays, and lack of transparency in information have been found, which cause retirees difficulties in accessing their entitlements. This study uses normative legal research methods with a statute approach and case approach, based on a study of banking regulations, consumer protection, and the social security system. The results of this research indicate that maladministration in pension fund payments can be categorized as a violation of consumer rights as regulated in Law No. 8 of 1999 on Consumer Protection and is contrary to the principles of prudence, transparency, and accountability in banking. The available legal protection mechanisms are divided into preventive measures, such as strengthening regulations and supervision, and repressive measures through internal complaints in banks, dispute resolution through the OJK and LAPS-SJK, up to civil lawsuits in court. However, challenges such as weak supervision, limited legal literacy, and the position of pensioners as vulnerable groups remain the main obstacles. Therefore, comprehensive legal protection needs to be strengthened, involving the government, PT Taspen, partner banks, and law enforcement agencies, to guarantee legal certainty, justice, and benefits for pension beneficiaries.